DEVELOPMENT OF REDOX REACTION LEARNING MEDIA BASED ON MULTIPLE REPRESENTATIONS - Muhammad Hisyam; Anita Fibonacci (Faculty of Education and Teacher Training, UIN (State Islamic University) Syarif Hidayatul, 2024)
The use of Information & Communication Technology (ICT) media is widespread in education, thus necessitating the facilitation of chemistry learning activities that guide students to study redox materials. This research aims to design a learning media product—an android application—on redox reaction materials based on MLR and to determine the feasibility level of this learning media product. The research method employed is a modified 4-D model reduced to 3-D, which includes the stages of define, design, and develop. The research instruments include interview sheets, student needs questionnaires, student learning styles, validation by subject matter and media experts, as well as student responses. The final results of this research reveal that the Android application learning media product on redox materials based on MLR is deemed feasible. This is supported by the Aiken's V coefficient value of 0.86 which is in the very feasible category, and limited development trials achieving an ideal percentage of 80.65%, falling into the feasible category.